title journal khatamirizki - Rizki, Putri Khatami (Just IT, 2011)
abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA abstract test in BAHASA INDONESIA Â abstract test in ENGLISH